2019
DOI: 10.21608/jappmu.2019.43014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Humic and Fulvic Acids Mixture Treatment on Productive and Reproductive Performance of Damascus Goat Bucks: 1. Thermoregulation, Body Weight, Sexual Desire and Semen Quality under Heat Stress Condition

Abstract: The objective of this study was to determine effect of humates, HTs (humic and fulvic acid mixture) on thermoregulation, body weight, sexual desire and semen quality of Damascus goat bucks under summer hot condition. The experimental work of this study was carried out at Sheep and Goats Breeding Research Department, Animal Production Research Institute. The experimental period lasted for 5 months, two months as primary period (April-May) and three months (Jun-August, 2017) as a semen collection period. During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Also, Li et al (2021) observed that adding 30 mM of Lp to semen extender had favourable results on the TM of post-thawed donkey sperm. In addition, our results are in agreement with Xiao et al (2018) and Abdel-Khalek et al (2019) in bucks, who reported a beneficial effect of FA on sperm motility. These results can be explained by the fact that these compounds may protect the sperm membrane against protein dephosphorylation and cause them to improve sperm motility after freeze-thawing process (Fu et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Also, Li et al (2021) observed that adding 30 mM of Lp to semen extender had favourable results on the TM of post-thawed donkey sperm. In addition, our results are in agreement with Xiao et al (2018) and Abdel-Khalek et al (2019) in bucks, who reported a beneficial effect of FA on sperm motility. These results can be explained by the fact that these compounds may protect the sperm membrane against protein dephosphorylation and cause them to improve sperm motility after freeze-thawing process (Fu et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…( 2018 ) and Abdel‐Khalek et al. ( 2019 ) in bucks, who reported a beneficial effect of FA on sperm motility. These results can be explained by the fact that these compounds may protect the sperm membrane against protein dephosphorylation and cause them to improve sperm motility after freeze‐thawing process (Fu et al., 2018 ).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations